(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Methods/Analysis Ultra-wideband (UWB) is the technology that can leverage broadband wireless services. UWB channels provide large bandwidth and help in supporting plethora of services and applications in cost-effective fashion. In other words, UWB can take the wireless communications and the utility of such networks to the next level. However, the existing nature of MAC protocol needs to be improved. Findings Therefore it is essential to have distributed, scalable and efficient MAC protocol in order to exploit UWB channels. The recent DEX based MAC protocol proposed by Cai et al. employs geometry distance to determine exclusive region in DEX protocol. They have not explored the Received Signal Strength (RSS) for the purpose. Novelty /Improvement In this paper we study the Received Signal Strength Indicator (RSSI) for determining the exclusive region and reserve it for users to have effective and fair sharing of resources in distributed and asynchronous manner. With our approach we quantify network performance. We implement the RSS for Optimization of Distributed Exclusive Region Based MAC Protocol (DEXRSSMAC) using NS2. Our simulations show the performance comparison of our protocol with existing ones such as EEDRP and DLBOP.